07. RETROSPECTIVE ANALYSIS OF SALVAGE SURGERY FOR LOCAL PROGRESSION OF BRAIN METASTASIS PREVIOUSLY TREATED WITH STEREOTACTIC IRRADIATION: DIAGNOSTIC CONTRIBUTION, FUNCTIONAL OUTCOME, AND PROGNOSTIC FACTORS. (4th August 2020) - Mitsuya, Koichi; Deguchi, Shoichi; Hayashi, Nakamasa; Harada, Hideyuki; Nakasu, Yoko
Abstract: BACKGROUND: Stereotactic irradiation (STI) is a primary treatment for patients with newly diagnosed brain metastases. Some of these patients experience local progression, which is difficult to differentiate from radiation necrosis, and difficult to treat. Just a few studies have clarified the prognosis and effectiveness of salvage surgery after STI. We evaluated the diagnostic value and improvement of functional outcomes after salvage surgery. METHODS: We evaluated patients with brain metastases treated with salvage surgery for local progression from October 2002 to July 2019. These patients had undergone salvage surgery based on magnetic resonance imaging findings and/or clinical evidence of post-STI local progression and stable systemic disease. We employed two prospective strategies according to the eloquency of the lesions. Lesions in non-eloquent areas had been resected completely with a safety margin, utilizing a fence-post method; while lesions in eloquent areas had been treated with minimal resection and postoperative STI. Prognostic factors for survival were analyzed. RESULTS: Fifty-four salvage surgeries had been performed on 48 patients. The median age of patients was 64 years. The median diameter of the enhanced lesions was 35 mm (range 19–58 mm). The median overall survival was 20.2 months from salvage surgery and 37.5 months from initial STI. Primary cancers were lung 31, breast 9, and others 8. Local recurrence developed in 13 of 54 lesions (24%). Leptomeningeal dissemination occurred after surgery in 3 patients (5.6%). Primary breast cancer (breast vs. lung: HR: 0.17), (breast vs. others: HR: 0.08) and RPA class 1–2 (RPA 1 vs. 3, HR: 0.13), (RPA 2 vs 3, HR: 0.4) were identified as good prognostic factors for overall survival (OS) in multivariate analyses. CONCLUSION: We insist that salvage surgery leads to rapid improvement of neurological function and clarity of histological diagnosis. Salvage surgery is recommended for large lesions especially with surrounding edema either in eloquent or non-eloquent areas.